Swietenolide diacetate from the seeds of Swietenia macrophylla - Goh, B.H.; Abdul Kadir, H.; Abdul Malek, S.N.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C31H38O10 [systematic name: (R,4R,4aR,6aS,7R,8S,10R,11S)-methyl ,10-diacetoxy-4-(3- furyl)-4a,7,9,9-tetramethyl-2,13-dioxo 1,4,4a,5,6,6a,7,8,9,10,- 11,12-dodecahydro-7,11-methano-2H-cycloocta[f][2]benzopyran-8-acetate], was isolated from the seeds of Swietenia macrophylla. The molecule contains four six-membered rings connected together in the shape of a bowl; one of the inner rings adopts a twisted chair conformation owing to the carbon–carbon double bond. The furyl substitutent is connected to an outer ring, and it points away from the bowl cavity.